Evaluation of a mainstream genetic testing program for women with ovarian or breast cancer. Issue 5 (30th January 2022) - Ip, Emilia; Young, Alison Luk; Scheinberg, Tahlia; Harrison, Michelle; Beale, Philip; Goodwin, Annabel
Abstract: Introduction: Mainstream genetic testing refers to genetic testing arranged by a patient's treating specialist. The aim of this study was to retrospectively review a Sydney‐based ovarian cancer mainstream genetic testing program. Methods: A Cancer Genetics Service (CGS)‐supported mainstream genetic testing program was commenced in 2015. The CGS provided training, paperwork and ongoing and adaptable advice regarding appropriate genes for testing and interpretation of results. Written and electronic medical records were reviewed until August 2019 to assess patient and family history characteristics, genetic testing eligibility, results and posttest management for women who had testing coordinated via mainstreaming or by the CGS. Results: Genetic testing was arranged for 289 women with ovarian cancer. Prior to 2017, 44% of genetic tests were mainstreamed, compared with 76% of tests from 2017 onwards. CGS was more likely to arrange testing for women with a strong family history of cancer and nonserous pathology. Germline pathogenic variants were detected in 13.7% (19/138) of women who had mainstream testing and 20.3% (14/69) of women tested by the CGS. Referral for posttest counseling occurred for pathogenic variant carriers identified through mainstreaming. Conclusion: This study demonstrated successful uptake of a mainstream ovarian cancer genetic testing program by medical oncologists, as evidenced by higher proportion and absolute numbers of eligible ovarian cancer patients accessing genetic testing through this pathway over time. The genetic testing criteria were appropriately assessed by oncologists and posttest referral occurred where required.